PENGARUH KOMPONEN ARUS KAS, LABA AKUNTANSI DAN DIVIDEND YIELD TERHADAP RETURN SAHAM (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI BEI PERIODE 2011-2013) - Widyanto Faisal Latief; Agus Purwanto (Diponegoro Journal of Accounting, 2015)
This study aims to analyze the influence of three components of cash flow, net profit and dividend yield to the stock return on manufactur industries listed in Indonesian Stock Exchange (IDX) during 2011 to 2013. This study uses 105 samples of manufacturing firms that listed in Indonesian Stock Exchange (IDX) during 2011 to 2013. The sampling method used for this study is purposive sampling. Type of the data used is secondary data. Data analysis used are descriptive statistics, classical assumption tests and multiple regression analysis. Variables used in this study are variable cash flow from operating, cash flow from invesment,  cash  flow  from  financing,  net  profit  and  dividend  yield  as  an  independent variable; Stock Return as an dependent variable. The result showed that operation cash flow has positive and significantly impacted the stock return. invesment cash flow has positive and not significant impact to the stock return. financing cash flow has positif and significant impact to the stock return. Accounting profit has positive and not significantly impacted the stock return Meanwhile dividend yield has negative and not significant impact to the stock return.